Epidurals and sciatica - Arden, N (2002)
Sciatica is a common musculoskeletal condition associated with considerable pain in the acute stages, but which carries a good long term prognosis. Epidural corticosteroid injections have been used for almost 50 years in this condition, however the evidence from randomised controlled trials is far from conclusive. Although epidural corticosteroid injections may offer some short term pain relief, they offer no medium or long term benefits, either in terms pain, return to work or need for surgery. Their exact role in the place in the management of sciatica in uncertain. But they should certainly not be used until the patient has received a suitable course of simple measures such as analgesia and physiotherapy.